1993
DOI: 10.1099/0022-1317-74-2-183
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of the murine coronavirus surface glycoprotein is not required for fusion activity

Abstract: A cDNA copy of the murine coronavirus [otherwise known as murine hepatitis virus (MHV)] surface (S) glycoprotein gene was isolated and expressed in DBT cells by using a recombinant vaccinia virus system. The expressed S protein induced extensive syncytium formation at neutral pH. Oligonucleotide mutagenesis was used to engineer an S protein gene in which codons for the proteolytic cleavage site, Arg-Arg-Ala-Arg-Arg, were replaced with an equal number of codons for amino acids with aliphatic or aliphatic hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 50 publications
4
55
0
Order By: Relevance
“…S2, which is more conserved (9, 11), forms the membrane-anchored stalk region (18) and mediates viral-host cell fusion (13,(19)(20)(21). Cleavage between S1͞S2 is not an absolute requirement for the fusion of CoV (4,11,17,[21][22][23][24], and the available data suggest that the S protein of SARS-CoV is not cleaved into subunits (4, 9, 17).The SARS-CoV S protein shares little amino acid similarity with other CoV (9). However, S2 contains two predicted amphipathic ␣-helical regions, with a 4,3 heptad repeat (HR), characteristic of coiled coils (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S2, which is more conserved (9, 11), forms the membrane-anchored stalk region (18) and mediates viral-host cell fusion (13,(19)(20)(21). Cleavage between S1͞S2 is not an absolute requirement for the fusion of CoV (4,11,17,[21][22][23][24], and the available data suggest that the S protein of SARS-CoV is not cleaved into subunits (4, 9, 17).The SARS-CoV S protein shares little amino acid similarity with other CoV (9). However, S2 contains two predicted amphipathic ␣-helical regions, with a 4,3 heptad repeat (HR), characteristic of coiled coils (9).…”
mentioning
confidence: 99%
“…S2, which is more conserved (9,11), forms the membrane-anchored stalk region (18) and mediates viral-host cell fusion (13,(19)(20)(21). Cleavage between S1͞S2 is not an absolute requirement for the fusion of CoV (4,11,17,(21)(22)(23)(24), and the available data suggest that the S protein of SARS-CoV is not cleaved into subunits (4,9,17).…”
mentioning
confidence: 99%
“…It has been considered that cleavage of the S protein is an important step in fusion activity (Frana et al, 1985;, which is very similar to the mechanisms of fusion-activation observed in other fusogenic RNA viruses (White, 1990). However, it has recently been found that by expressing uncleaved S proteins the cleavage event is not an absolute requirement for fusion activity (Stauber et al, 1993;. The S protein has been shown to be directly or indirectly implicated in the pathogenicity of MHV (Fleming et al, 1983;Dalziel et al, 1986).…”
Section: Introductionmentioning
confidence: 86%
“…First, a "wild-type'' S gene cDNA which differs from the S gene sequence published by Schmidt et al [20] at positions 793: G to C; 794: C to G; 1855: A to G and 3281: C toT.The S protein expressed from this gene is fusogenic [21]. Second, a variant S gene cDNA which differs from the published sequence at positions 793: G to C; 794: C to G; 1090: T to C and 1855: A to G.The S protein expressed from this gene is not fusogenic [unpublished observation].…”
Section: Construction and Expression Of Mhv-jhm Proteinsmentioning
confidence: 98%
“…For indirect immunofluorescence cultures of DBTcells were infected with VV-wt, VV-SwiIdtype and VV-S354CR at a multiplicity of infection (m.0.i.) of 1 [lo, 21,23,241. The cells were fixed with 3.5% buffered formaldehyde and incubated with monoclonal antibodies against MHV-JHM-N or S proteins, followed by incubation with fluorescein isothiocyanate-conjugated goat anti-mouse IgG (Dako, Copenhagen, Denmark).…”
Section: Construction and Expression Of Mhv-jhm Proteinsmentioning
confidence: 99%